Broccoli production depending on nitrogen and potassium rates on seedlings fertigation - Lima Silva, Priscilla Nataly de [UNESP]; Souza, Luis Gustavo de [UNESP]; Narciso Redigolo, Mateus Vinicius [UNESP]; Inacio Cardoso, Antonio Ismael [UNESP] (Univ Estadual Mato Grosso Sul, 2018)
Considering there are few researches about the influence of nitrogen and potassium application in brassica seedling production, this work was carried out to evaluate the effect of these nutrient rates in seedling fertigation grown in coconut fiber substrate on broccoli production. A randomized blocks experimental design, in a factorial scheme with four N rates (0, 80, 160 and 240 mg L-1) and four K rates (0, 100, 200 and 300 mg L-1) in fertigation of seedlings with four replications was used. Macronutrients quantity and vegetative seedlings characteristics, such as the number of leaves, plant height, stem diameter, shoot fresh and dry weight were evaluated, as well as, at harvesting, the number of leaves, diameter, fresh and inflorescence dry weight. Data were submitted to variance and regression analysis. The characteristics analyzed in the plants were not affected by the potassium rates. It was obtained a linear increase for all the vegetative characteristics and accumulation of N, K, Ca and Mg of the seedlings, as well as the fresh and dry weight of the inflorescences with the increase of the rates of N tested.
Keywords: fertilization; Brassica oleraceae var. italica; nutrients extraction; seedling production